Melanoma arising in a patient with ataxia‐telangiectasia: A call for full skin examinations in this patient population. Issue 4 (15th May 2020) - Oska, Sandra; Zarbo, Allison; Yeager, Danielle; Friedman, Ben J.; Shwayder, Tor
Abstract: Ataxia‐telangiectasia (A‐T) is an autosomal recessive, multisystem disorder characterized by cerebellar ataxia and oculocutaneous telangiectasias that present in early childhood. Increased incidence of malignancy is also associated with A‐T. Hematopoietic malignancies occur most commonly, with a majority being lymphoid cancers; however, there is a risk for other malignancies, such as breast, gastric, and other solid tumors. Herein, we report the case of a 28‐year‐old woman with A‐T with melanoma.